2003
DOI: 10.1167/iovs.02-0815
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ATP-Sensitive Potassium Channel: A Novel Site for Neuroprotection

Abstract: These results suggest that BK and diazoxide protect retinal neurons against glutamate excitotoxicity by opening the Mit K (ATP) channel. It is suggested that opening of the Mit K (ATP) channel inhibited glutamate-induced generation of superoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
2
39
1
Order By: Relevance
“…It is well documented that K ATP channel, especially mitoK ATP channel, may be a novel protective target for neuron and astrocyte (Yamauchi et al, 2003;Busija et al, 2004). Accumulating evidence has showed that the amount of mitoK ATP channels located in brain cells is at least sixfold higher than that in heart cells (Bajgar et al, 2001;Lacza et al, 2003), indicating an essential role of mitoK ATP channel in the physiology and pathology of CNS.…”
Section: Iptakalim Inhibits Neuroinflammation F Zhou Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that K ATP channel, especially mitoK ATP channel, may be a novel protective target for neuron and astrocyte (Yamauchi et al, 2003;Busija et al, 2004). Accumulating evidence has showed that the amount of mitoK ATP channels located in brain cells is at least sixfold higher than that in heart cells (Bajgar et al, 2001;Lacza et al, 2003), indicating an essential role of mitoK ATP channel in the physiology and pathology of CNS.…”
Section: Iptakalim Inhibits Neuroinflammation F Zhou Et Almentioning
confidence: 99%
“…Thus, mitoK ATP channels may be an important molecular target for inhibiting microglia-mediated neuroinflammation and for treating neuroinflammation-related neurodegenerative disorders. Although Liss et al (2005) reported that genetic inactivation of Kir6.2 resulted in a selective rescue of substantia nigra dopaminergic neurons in a MPTP model of dopaminergic degeneration, there were a large number of evidences for benefits afforded by activating mitoK ATP in ischemia and degeneration (Yamauchi et al, 2003;Busija et al, 2004;Farkas et al, 2005a, b). This discrepancy may be owing to the difference between the opening of mitoK ATP channels and genetic inactivation of Kir6.2.…”
Section: Iptakalim Inhibits Neuroinflammation F Zhou Et Almentioning
confidence: 99%
“…The neuroprotective effect of bradykinin in glutamate excitotoxicty has been demonstrated in retinal neuron cells by opening the mitochonrial adenosine triphosphate (ATP)-sensitive potassium channels (Mit K (ATP)) . Glutamate is thought to be induced and the superoxides are thought to be inhibited by the opening of Mit K(ATP) channels (30). ACE inhibitors may have helped in opening the Mit K(ATP) channels by preventing bradykinin degradation via inhibition of kininase-II and in exhibiting a neuroprotective effect in glutamate neurotoxicity by reducing the glutamate-induced superoxide radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that K ATP channels play an important role in enhancing retinal resistance against ischemic insult (10,12,14,26). Retinal ischemic injury induces cell death of retinal neurons by excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…ATP-sensitive potassium channels (K ATP channels) in the mitochondrial or plasma membrane of retinal cells may provide protection against retinal ischemia (10,11). Yamauchi and colleagues suggested that opening of mitochondrial K ATP channels can inhibit glutamate.…”
Section: Introductionmentioning
confidence: 99%